2009
DOI: 10.1007/s11270-009-9997-8
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exclusion and Copper Translocation in Black Spruce Needles

Abstract: Current-year, 1-year-old, and 2-year-old needles were collected separately on 37 black spruce (Picea mariana Mill. B.S.P.) trees located on a heavy metal contamination gradient around the smelter in Murdochville, Québec (Canada). Needles were analyzed separately by year for the concentrations of Pb and Cu, a nonessential and an essential metal, respectively. Lead concentrations increased significantly with needle age in the highly contaminated area near the smelter. In contrast, Cu concentrations decreased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Moreover, some recent data for the black spruce needles supported the previous hypothesis and confirmed that an active translocation of essential metals, particularly Cu, takes place from senescent to non-senescent parts of a plant. However, the results for Pb, as a nonessential metal, were in accordance with a hypothesis that the passive sequestration of toxic metals was attained in the senescing foliage as a detoxification process (Aznar et al, 2009).…”
Section: Trace Elements In Tree Leavessupporting
confidence: 86%
“…Moreover, some recent data for the black spruce needles supported the previous hypothesis and confirmed that an active translocation of essential metals, particularly Cu, takes place from senescent to non-senescent parts of a plant. However, the results for Pb, as a nonessential metal, were in accordance with a hypothesis that the passive sequestration of toxic metals was attained in the senescing foliage as a detoxification process (Aznar et al, 2009).…”
Section: Trace Elements In Tree Leavessupporting
confidence: 86%
“…In case of the walnut trees, the concentration of Cu in old leaves was just 8% of the maximum Cu value measured in the younger mature leaves [23]. Also, some recent data for the black spruce needles, supporting a previous hypothesis, confirmed that an active translocation of essential metals, particularly Cu, takes place from senescent to nonsenescent parts of a plant [24]. The authors also pointed that, on the contrary, the results obtained for Pb, as nonessential metal, were in accordance with a hypothesis that the passive sequestration of toxic metals was attained in the senescing foliage as a detoxification process.…”
Section: Total Element Content In Leaves and Comparison With Bulk Depsupporting
confidence: 68%
“…Popović et al (2010) and Tomašević et al ( 2011 ) found that the seasonal accumulation of the examined elements in leaves of Aesculus hippocastanum L. was more regular. Aznar et al ( 2009 ) supposed that Pb, as a nonessential metal, remained in the foliage as part of a detoxification process. Hovmand et al ( 2009 ) studied the origin of Pb in Norway spruce and Tomašević and Aničić ( 2010 ) the origin of Pb in horse chestnut tree leaves.…”
Section: Discussionmentioning
confidence: 99%